Dielectric properties of (1-x)SrFe1/2Nb1/2O3-xBaZn1/3Ta2/3O3 ceramics - Thanatep Phatungthane (2018)
In this work, (1-x)SrFe1/2Nb1/2O3-xBaZn1/3Ta2/3O3 ((1-x)SFN-xBZT) ceramics with 0.02 ≤ x ≤ 0.11 were synthesized via a solid state reaction method. A phase formation analysis using the x-ray diffraction technique (XRD) showed that the ceramic samples exhibited a pure phase perovskite for x ≤ 0.10 compositions, indicating that the solubility limit of BZT in SFN is very low. Adding BZT enhanced the dielectric constant and reduced the dielectric loss. Very high dielectric constants (>40,000) were observed for the x = 0.10 samples. The dielectric property investigation also revealed that all samples exhibited dielectric relaxor behavior. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.